Chemical Composition and α-Glucosidase Inhibitory Activity of Vietnamese Citrus Peels Essential Oils - Nguyen Hai Dang; Pham Huong Nhung; Bui Thi Mai Anh; Dinh Thi Thu Thuy; Chau Van Minh; Nguyen Tien Dat (Journal of Chemistry)
Background. Inhibition of α-glucosidase is an important factor to control postprandial hyperglycemia in type 2 diabetes mellitus. Citrus essential oils (CEO) are among the most widely used essential oils, and some of them exhibited promising antidiabetic effect. However, the α-glucosidase inhibition of CEO has not been investigated so far. The present work aims to evaluate the α-glucosidase inhibition of essential oils from six Vietnamese Citrus peels. Methods. The chemical composition of essential oils obtained by hydrodistillation from six Citrus peels was analyzed by GC-MS. All essential oils were tested for their inhibitory activity on α-glucosidase using p-nitrophenyl-α-D-glucopyranoside as substrate. Results. In Buddha’s hand and lime peels, the major components were limonene (59.0–61.31%) and γ-terpinene (13.98–23.84%) while limonene (90.95–95.74%) was most abundant in pomelo, orange, tangerine, and calamondin peels. Among the essential oils, the Buddha’s hand oil showed the most significant α-glucosidase inhibitory effect with the IC50 value of 412.2 μg/mL. The combination of the Buddha’s hand essential oil and the antidiabetic drug acarbose increased the inhibitory effect. Conclusions. The results suggested the potential use of Buddha’s hand essential oil as an alternative in treatment of type 2 diabetes mellitus.